Antimicrobial and cytotoxic effects of phosphoric acid solution compared to other root canal irrigants - Maíra PRADO; Emmanuel João Nogueira Leal da SILVA; Thais Mageste DUQUE; Alexandre Augusto ZAIA; Caio Cezar Randi FERRAZ; José Flávio Affonso de ALMEIDA; Brenda Paula Figueiredo de Almeida GOMES (University of São Paulo, 2015)
Phosphoric acid has been suggested as an irrigant due to its effectiveness in removing the smear layer. Objectives : The purpose of this study was to compare the antimicrobial and cytotoxic effects of a 37% phosphoric acid solution to other irrigants commonly used in endodontics. Material and Methods : The substances 37% phosphoric acid, 17% EDTA, 10% citric acid, 2% chlorhexidine (solution and gel), and 5.25% NaOCl were evaluated. The antimicrobial activity was tested against Candida albicans, Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Actinomyces meyeri, Parvimonas micra, Porphyromonas gingivalis, and Prevotella nigrescens according to the agar diffusion method. The cytotoxicity of the irrigants was determined by using the MTT assay. Results : Phosphoric acid presented higher antimicrobial activity compared to the other tested irrigants. With regard to the cell viability, this solution showed results similar to those with 5.25% NaOCl and 2% chlorhexidine (gel and solution), whereas 17% EDTA and 10% citric acid showed higher cell viability compared to other irrigants. Conclusion : Phosphoric acid demonstrated higher antimicrobial activity and cytotoxicity similar to that of 5.25% NaOCl and 2% chlorhexidine (gel and solution).